Pengaruh Spesies Inang dan Sumber Nutrisi Terhadap Produksi Spora Fungi Mikoriza Arbuskula - Delvian, Delvian (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2008)
An experiment to study the effect of host species and source of nutrient on spore production of an ArbusculeMycorrhizal Fungus, Gigaspora margarita, has been carried out. Combination treatments studied consisted ofhost species (Zea mays and Pueraria javanica) and nutrient factor (no fertilizer, fertilizer and Red Hyponex).Growth medium used was a mix of soil and sand in 1: 1 ratio (v/v) which was sterilized. Results of the experimentshowed that spore production of G. margarita was affected by host species and also by nutrient applied, thoughthere was no interaction between the two factors. However, P. javanica produced more spore than Z. mays.Treatment with Red Hyponex result much higher spores than others, but however without fertilizer produced morespores than Urea, TSP and KCl fertilizers.